Prevalence of Aggregatibacter actinomycetemcomitans in Sudanese patients with aggressive periodontitis: a case-control study - Elamin, A.; Albandar, J. M.; Poulsen, K.; Ali, R. W.; Bakken, V. (Journal of periodontal research, 2011)
Elamin A, Albandar JM, Poulsen K, Ali RW, Bakken V. Prevalence ofAggregatibacter actinomycetemcomitansin Sudanese patients with aggressive periodontitis: a case–control study. J Periodont Res 2011; 46: 285–291.©2011 John Wiley & Sons A/S Background and Objective:  Aggregatibacter actinomycetemcomitans is considered a possible etiological agent for aggressive periodontitis. The aim of this study was to determine the prevalence of the JP2 clone and non‐JP2 genotypes of A. actinomycetemcomitans in the subgingival plaque of patients with aggressive periodontitis and controls among Sudanese high‐school students. Material and Methods:  In a previous study we examined a large representative sample of students attending high schools in Khartoum, Sudan. In this population, 17 patients with aggressive periodontitis and 17 controls (14–19 years of age) consented to participate in the present study. The subjects underwent a clinical periodontal examination, and subgingival dental plaque samples were collected using paper points. The presence of the A. actinomycetemcomitans JP2 clone and non‐JP2 genotypes were assessed using loop‐mediated isothermal amplification (LAMP) and the PCR. Results:  The JP2 clone of A. actinomycetemcomitans was not detected in the subgingival plaque of either the cases or the controls. Non‐JP2 types of A. actinomycetemcomitans were detected in the subgingival plaque of 12 (70.6%) patients with aggressive periodontitis and from only one (5.9%) control subject, showing a significantly higher frequency of detection in cases than in controls (p = 0.0001). The odds ratio for the detection of A. actinomycetemcomitans in the subgingival plaque of the patients with aggressive periodontitis was 38.4 (95% confidence interval: 4.0–373.0; p = 0.002). The PCR and LAMP methods showed identical results pertaining to the identification of non‐JP2 types of A. actinomycetemcomitans. Conclusions:  The JP2 clone of A. actinomycetemcomitans was not detected in the subgingival plaque of high school subjects in Sudan. The detection of non‐JP2 types of A. actinomycetemcomitans may be a useful marker of increased risk for development of aggressive periodontitis in young subjects.